Anthropometric measurements among four Asian countries in designing sitting and standing workstations - Abd Rahman, Nurul Izzah; Md Dawal, Siti Zawiah; Yusoff, Nukman; Mohd Kamil, Nabilla Sofia (Springer, 2018)
An anthropometric database for sitting and standing dimensions for Malaysian operators was developed based on the measurements from 146 male and 168 female participants (18–45 years old). The anthropometric data were subsequently compared to those from three selected Asian countries, focussing on the sitting and standing posture dimensions. Thirty-six anthropometric dimensions were selected for comparison based on common availability among the four countries. The results indicated that the Indonesians were the tallest (male: 172 cm, female: 159 cm) among the four countries, whereas the Filipinos were the shortest for both male and female (male: 167 cm, female: 153.9 cm). Filipinos and Malaysian data were almost similar and appear to have the smallest values for eye height (male: 155 cm, female: 143 cm) and elbow height (male: 104 cm, female: 96 cm). The knowledge of variations in the population is useful in designing sound workstations and facilities for the betterment of the industrial environment.